In-situ laboratory X-ray diffraction applied to assess cement hydration - de Matos, Paulo R.; Andrade Neto, José S.; Jansen, Daniel; De la Torre, Angeles G.; Kirchheim, Ana Paula; Campos, Carlos E.M. (Cement and Concrete Research, 2022)
In-situ X-ray diffraction (XRD) is a powerful tool to assess the hydration of cementitious materials, providing time-resolved quantitative analysis with reasonable accuracy without disturbing sample. However, the lack of guidelines and well-established procedures for data collection and analysis is the limiting factor for spreading this technique. This paper discussed using in-situ laboratory XRD to assess cement hydration. The first part was dedicated to a literature review on the topic. Then, experimental strategies were discussed, and recommendations related to the data analysis routine were drawn; the advantages and limitations of this technique were also discussed. We can conclude that the critical factors for a successful analysis are the choice of an adequate experimental setup with good statistics and low measurement time, the proper consideration of different amorphous contributions in the XRD pattern, and a good data analysis routine. Independent techniques are highly recommended to support the in-situ XRD data.
CRIS-Team Scopus Importer:2022-10-07
Keywords: Cement; Hydration; In-situ XRD; Laboratory XRD; X-ray diffraction